Motivation program in small and medium-sized manufacturing enterprises based on the preference for needs - Hitka, Milos; Lorincova, Silvia; Rowland, Zuzana; Lipoldova, Martina (Journal of Business Economics and Management, 2023)
Motivation and meeting the employee needs as a part of human resource management fundamentally affect the improvement of job performance and corporate culture. The research fills in the research gap in the field of the definition of the level of motivation factors in small and medium-sized manufacturing enterprises following the preferences for their motivation needs in terms of the selected socio-demographic characteristics such as gender, age, completed education, and job position. A questionnaire was used to determine the level of motivation needs. The proposal of motivation factors as a part of the motivation programme is defined according to selected sociodemographic factors. Findings that a significant increase in motivation needs relating to finance, and work conditions occurred due to the COVID-19 pandemic can be considered a result of the study. The level of motivation does not vary in terms of gender and age. The differences are determined in terms of job position and education. The proposed motivation programme is tailored to the preferences of employees.